Perceptions and evaluations of front-line health workers regarding the Brazilian National Program for Improving Access and Quality to Primary Care (PMAQ): a mixed-method approach - Fabiana da Cunha Saddi; Matthew J. Harris; Germano Araújo Coelho; Raquel Abrantes Pêgo; Fernanda Parreira; Wellida Pereira; Ana Karoline C. Santos; Heloany R. Almeida; Douglas S. Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: Although it is well known that a successful implementation depends on the front-liners' knowledge and participation, as well as on the organizational capacity of the institutions involved, we still know little about how front-line health workers have been involved in the implementation of the Brazilian National Program for Improving Access and Quality to Primary Care (PMAQ). This paper develops a contingent mixed-method approach to explore the perceptions of front-line health workers - managers, nurses, community health workers, and doctors - regarding the PMAQ (2nd round), and their evaluations concerning health unit organizational capacity. The research is guided by three relevant inter-related concepts from implementation theory: policy knowledge, participation, and organizational capacity. One hundred and twenty-seven health workers from 12 primary health care units in Goiânia, Goiás State, Brazil, answered semi-structured questionnaires, seeking to collect data on reasons for adherence, forms of participation, perceived impact (open-ended questions), and evaluation of organizational capacity (score between 0-10). Content analyses of qualitative data enabled us to categorize the variables "level of perceived impact of PMAQ" and "reasons for adhering to PMAQ". The calculation and aggregation of the means for the scores given for organizational capacity enabled us to classify distinct levels of organizational capacity. We finally integrated both variables (Perceived-Impact and Organizational-Capacity) through cross-tabulation and the narrative. Results show that nurses are the main type of professional participating. The low organizational capacity and little policy knowledge affected workers participation in and their perceptions of the PMAQ.